2012
DOI: 10.4062/biomolther.2012.20.4.399
|View full text |Cite
|
Sign up to set email alerts
|

Cell Death by Polyvinylpyrrolidine-Coated Silver Nanoparticles is Mediated by ROS-Dependent Signaling

Abstract: Silver nanoparticles (AgNPs) are widely used nanoparticles and they are mainly used in antibacterial and personal care products. In this study, we evaluated the effect of AgNPs on cell death induction in the murine dendritic cell line DC2.4. DC2.4 cells exposed to AgNPs showed a marked decrease in cell viability and an induction of lactate dehydrogenase (LDH) leakage in a time- and dose-dependent manner. In addition, AgNPs promoted reactive oxygen species (ROS)-dependent apoptosis and AgNP-induced ROS triggere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 37 publications
5
42
0
Order By: Relevance
“…Further, polyvinylpyrrolidine-coated AgNPs inhibited cell proliferation and viability, and increased LDH leakage, in a time-and concentration-dependent manner in the murine dendritic DC2.4 cell line (Kang et al). 75 The results from our experiments and the previous literature suggest that AgNPs can reduce the membrane potential of MDA-MB-231 cells. 73 …”
supporting
confidence: 71%
See 4 more Smart Citations
“…Further, polyvinylpyrrolidine-coated AgNPs inhibited cell proliferation and viability, and increased LDH leakage, in a time-and concentration-dependent manner in the murine dendritic DC2.4 cell line (Kang et al). 75 The results from our experiments and the previous literature suggest that AgNPs can reduce the membrane potential of MDA-MB-231 cells. 73 …”
supporting
confidence: 71%
“…ROS target mitochondria and cause DNA damage and apoptosis. 75 Earlier studies have suggested that AgNPs are inducers of ROS in a variety of cells. 10,20,65,76 The exposure of MDA-MB-231 cells to AgNPs could result in the production of ROS, which could explain the outcomes of metabolic and toxicological problems (Figure 8).…”
Section: Effect Of B-agnps and F-agnps On Ros Generationmentioning
confidence: 99%
See 3 more Smart Citations